Star wars. The phantom menace [videorecording (Blu-Ray)] - Lucas, George, 1944-; Neeson, Liam; Jackson, Samuel L.; McGregor, Ewan, 1971-; Portman, Natalie, 1981- (LucasFilm, 2019)
Stranded on the planet Tatooine after rescuing Queen Amidala of Naboo, Jedi apprentice Obi-Wan Kenobi and his Jedi Master Qui-Gon Jinn discover nine-year-old Anakin Skywalker, a young slave. Gifted with the power of the Force, Anakin wins his freedom and leaves home to be trained as a Jedi. Back on Naboo, Anakin and the Queen face a massive invasion while the two Jedi confront a lethal foe named Darth Maul.